ρan-ρan - Hogg, Norman; Mulholland, Neil (punctum books, 2021)
"With the peristaltic gurglings of this gastēr-investigative procedural – a soooo welcomed addition to the ballooning corpus of slot-versatile bad eggs The Confraternity of Neoflagellants (CoN) – [users] and #influencers everywhere will be belly-joyed to hold hands with neomedieval mutter-matter that literally sticks and branches, available from punctum in both frictionless and grip-gettable boke-shaped formats.